Triglyceride to high-density lipoprotein cholesterol ratio is associated with diabetes incidence in non-obese individuals with normoglycemia: a retrospective cohort study based on individuals from East Asia - Huang, Zhenhua; Zhang, Xigang; Sun, Dayong; Yu, Ke (Frontiers in Endocrinology, 2024)
Background Although several studies have explored the association between the triglyceride to high-density lipoprotein cholesterol ratio (TG/HDL-c) and diabetes risk, most of these studies are cross-sectional and typically involve small sample sizes, limiting the ability to draw causal inferences. Additionally, there is currently a few studies specifically focusing on non-obese individuals. Consequently, we conducted a retrospective cohort study to investigate the impact of TG/HDL-c on the risk of developing diabetes among non-obese, normoglycemic individuals across East Asian countries.Methods This secondary retrospective cohort study recruited 85,029 non-obese individuals with normal glycemic levels from East Asian countries (China and Japan).We employed Cox proportional hazards regression models, incorporating cubic splines function for smooth curve fitting and using two-piecewise Cox regression for threshold effect analysis, to evaluate the nonlinear associations between baseline TG/HDL-c ratios and diabetes risk in non-obese individuals with normoglycemia. In addition, A range of subgroup and sensitivity analyses were performed to confirm the robustness of our results.Among the individuals included, the average age was 42.14 ± 11.88 years, and 37,944 participants (44.62%) were male. After adjusting for covariates, the study revealed a significant correlation between the TG/HDL-c ratio and the risk of diabetes among non-obese individuals (HR=1.37, 95%CI: 1.22-1.54). Furthermore, a non-linear correlation was observed between the TG/HDL-c ratios and the incidence of non-obese diabetes, with an inflection point of 1.36. Under this threshold, the TG/HDL-c ratio notably boosts diabetes risk in non-obese populations, with an HR of 2.38 (95% CI:1.57-3.59). Conversely, beyond the critical juncture, the upsurge in diabetes risk seems to level off, displaying no significant variation, with an HR of 1.18 (95% CI: 0.98-1.41).This study reveals a non-linear association between the TG/HDL-c ratios and the likelihood of diabetes in non-obese individuals from East Asia. Maintaining a ratio of TG/HDL-C below 1.36 significantly reduces diabetes risk. However, once the ratio of TG/HDL-C exceeds 1.36, reducing it does not substantially lower diabetes onset risk.